2001
DOI: 10.1152/jn.2001.85.4.1424
|View full text |Cite
|
Sign up to set email alerts
|

RPCH Modulation of a Multi-Oscillator Network: Effects on the Pyloric Network of the Spiny Lobster

Abstract: The neuropeptide red pigment concentrating hormone (RPCH), which we have previously shown to activate the cardiac sac motor pattern and lead to a conjoint gastric mill-cardiac sac pattern in the spiny lobster Panulirus, also activates and modulates the pyloric pattern. Like the activity of gastric mill neurons in RPCH, the pattern of activity in the pyloric neurons is considerably more complex than that seen in control saline. This reflects the influence of the cardiac sac motor pattern, and particularly the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…While a number of factors could potentially underlie the quantitative variability in responses across animals, differences in response to a given modulator have most often been attributed to the 'state' of the system; this in turn is often reflected in the starting parameters of the pattern, notably cycle frequency (Dickinson et al, 2001;Fu et al, 2007;Medler and Hulme, 2009;Nadim et al, 2008;Nagy and Dickinson, 1983;Nusbaum and Marder, 1989b;Sargeant, 2007). To explain this correlation, it has been suggested that membrane conductance is, on average, lower in preparations with low cycle frequency, with the consequence that a similar change in currents induced by the modulator will have a larger effect than in more rapidly cycling preparations (Fu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of factors could potentially underlie the quantitative variability in responses across animals, differences in response to a given modulator have most often been attributed to the 'state' of the system; this in turn is often reflected in the starting parameters of the pattern, notably cycle frequency (Dickinson et al, 2001;Fu et al, 2007;Medler and Hulme, 2009;Nadim et al, 2008;Nagy and Dickinson, 1983;Nusbaum and Marder, 1989b;Sargeant, 2007). To explain this correlation, it has been suggested that membrane conductance is, on average, lower in preparations with low cycle frequency, with the consequence that a similar change in currents induced by the modulator will have a larger effect than in more rapidly cycling preparations (Fu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although RPCH was originally identified based on its ability to affect the concentration of pigment granules in erythrophores, it has subsequently been shown to be highly pleiotropic, modulating the central pattern generating networks present in the STNS [223,228,246,[248][249][250][251][252] and CG [83], as well as the motor output of the swimmeret system [247]. Recently, RPCH was implicated in the mobilization of energy stores in Porcellio scaber [244].…”
Section: Red Pigment Concentrating Hormonementioning
confidence: 99%
“…These are all modulated by at least one of the neuropeptides present in the STNS. Post-inhibitory rebound in the LP neuron of Panulirus interruptus, for example, is enhanced in the presence of RPCH [248]. Weimann et al [168] showed that SDRNFLRFamide and TNRNFLFRamide enhance the ability of the DG neuron to produce plateau potentials, sometimes even causing it to fire in endogenous bursts.…”
Section: Modulation Of the Pyloric And Gastric Motor Patterns By Neurmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide RPCH (pQLNFSPGW-NH 2 ) is present in three distinctive neuroendocrine sites in crustaceans (including C. borealis): the pericardial organs, sinus gland and eyestalks (Christie et al, 1995;Fu et al, 2005a;Li et al, 2003;Pulver and Marder, 2002;Stemmler et al, 2006). RPCH is also found within the terminals of neurons projecting from anterior ganglia to the stomatogastric ganglion (STG) (Christie et al, 1997a;Nusbaum and Marder, 1988;Thirumalai and Marder, 2002) and it is considered an endogenous modulator of the stomatogastric nervous system (STNS) (Dickinson et al, 1993;Dickinson et al, 2001;Dickinson and Marder, 1989;Dickinson et al, 1990;Nusbaum and Marder, 1988).…”
Section: Introductionmentioning
confidence: 99%